(untitled) (Health and Biosciences, 2025)
This article presents an experience report of an investigative teaching sequence applied in an elementary and middle school in the municipality of Rio Bananal, Espírito Santo, Brazil. The aim was to help students understand the real reason behind smartphone consumption, with an emphasis on youth consumption, identifying companies’ planned obsolescence actions and the environmental and social consequences of this type of sales strategy. The data were collected through the application of an investigative teaching sequence in a high school class, where students conducted research on the concept of planned obsolescence, associating the data with the frequency of cell phone replacement by young people. In addition, a self-assessment of their own consumption was carried out, identifying the influence of this behavior on youth self-esteem and the environmental impacts related to the induced consumption of various products through planned obsolescence. At the end of the classes, the adolescents were able to identify how they are induced to consume, as well as the damage that misguided consumerism causes to their self-esteem. In addition, they were able to produce materials to raise awareness among other young people about the issue.